A BMP/Activin A Chimera Induces Posterolateral Spine Fusion in Nonhuman Primates at Lower Concentrations Than BMP-2. (18th August 2021) - Seeherman, Howard J.; Wilson, Christopher G.; Vanderploeg, Eric J.; Brown, Christopher T.; Morales, Pablo R.; Fredricks, Douglas C.; Wozney, John M.
Abstract : Background: Supraphysiologic bone morphogenetic protein (BMP)-2 concentrations are required to induce spinal fusion. In this study, a BMP-2/BMP-6/activin A chimera (BV-265), optimized for BMP receptor binding, delivered in a recombinant human collagen:CDHA [calcium-deficient hydroxyapatite] porous composite matrix (CM) or bovine collagen:CDHA granule porous composite matrix (PCM), engineered for optimal BV-265 retention and guided tissue repair, was compared with BMP-2 delivered in a bovine absorbable collagen sponge (ACS) wrapped around a MASTERGRAFT Matrix (MM) ceramic-collagen rod (ACS:MM) in a nonhuman primate noninstrumented posterolateral fusion (PLF) model. Methods: In vivo retention of 125 I-labeled-BV-265/CM or PCM was compared with 125 I-labeled-BMP-2/ACS or BMP-2/buffer in a rat muscle pouch model using scintigraphy. Noninstrumented PLF was performed by implanting CM, BV-265/CM, BV-265/PCM, or BMP-2/ACS:MM across L3-L4 and L5-L6 or L3-L4-L5 decorticated transverse processes in 26 monkeys. Computed tomography (CT) images were acquired at 0, 4, 8, 12, and 24 weeks after surgery, where applicable. Manual palpation, μCT (microcomputed tomography) or nCT (nanocomputed tomography), and histological analysis were performed following euthanasia. Results: Retention of 125 I-labeled-BV-265/CM was greater than BV-265/PCM, followed by BMP-2/ACS and BMP-2/buffer. The CM, 0.43 mg/cm 3 BMP-2/ACS:MM, and 0.05 mg/cm 3 BV-265/CM failed to generate PLFs. The 0.15-mg/cm 3 BV-265/CM or 0.075-mg/cm 3 BV-265/PCM combinations were partially effective. The 0.25-mg/cm 3 BV-265/CM and 0.15 and 0.3-mg/cm 3 BV-265/PCM combinations generated successful 2-level PLFs at 12 and 24 weeks. Conclusions: BV-265/CM or PCM can induce fusion in a challenging nonhuman primate noninstrumented PLF model at substantially lower concentrations than BMP-2/ACS:MM. Clinical Relevance: BV-265/CM and PCM represent potential alternatives to induce PLF in humans at substantially lower concentrations than BMP-2/ACS:MM.